Optimizing cell sourcing for clinical translation of tissue engineered ears *Portions of this research were presented at The New York Regional Society of Plastic Surgery Annual Meeting (March 2015, New York, NY), The American Association of Plastic Surgeons 94th Annual Meeting (April 2015, Scottsdale, AZ), The 60th Annual Meeting of the Plastic Surgery Research Council (May 2015, Seattle, WA), and the Northeastern Society of Plastic Surgeons 32nd Annual Meeting (September 2015, Philadelphia, PA). (5th December 2016) - Morrison, Kerry A; Cohen, Benjamin P; Asanbe, Ope; Dong, Xue; Harper, Alice; Bonassar, Lawrence J; Spector, Jason A
Abstract: Background . Currently, the major impediment to clinical translation of our previously described platform for the fabrication of high fidelity, patient-specific tissue engineered ears is the development of a clinically optimal cell sourcing strategy. A limited autologous auricular chondrocyte (AuC) supply in conjunction with rapid chondrocyte de-differentiation during in vitro expansion currently makes clinical translation more challenging. Mesenchymal stem cells (MSCs) offer significant promise due to their inherent chondrogenic potential, and large availability through minimally invasive procedures. Herein, we demonstrate the promise of AuC/MSC co-culture to fabricate elastic cartilage using 50% fewer AuC than standard approaches. Methods. Bovine auricular chondrocytes (bAuC) and bovine MSC (bMSC) were encapsulated within 10 mg ml −1 type I collagen hydrogels in ratios of bAuC:bMSC 100:0, 50:50, and 0:100 at a density of 25 million cells ml −1 hydrogel. One mm thick collagen sheet gels were fabricated, and thereafter, 8 mm diameter discs were extracted using a biopsy punch. Discs were implanted subcutaneously in the dorsa of nude mice (NU/NU) and harvested after 1 and 3 months. Results . Gross analysis of explanted discs revealed bAuC:bMSC co-culture discs maintained their size and shape, and exhibited native auricular cartilage-like elasticity after 1 and 3 months of implantation. Co-culture discs developed into auricular cartilage, with viable chondrocytes within lacunae, copious proteoglycan and elastic fiber deposition, and a distinct perichondrial layer. Biochemical analysis confirmed that co-culture discs deposited critical cartilage molecular components more readily than did both bAuC and bMSC discs after 1 and 3 months, and proteoglycan content significantly increased between 1 and 3 months. Conclusion . We have successfully demonstrated an innovative cell sourcing strategy that facilitates our efforts to achieve clinical translation of our high fidelity, patient-specific ears for auricular reconstruction utilizing only half of the requisite auricular chondrocytes to fabricate mature elastic cartilage.